Development of Agrotourism at Sukapulang Tourist Destination in Sukasetia Village, Cihaurbeuti District, Ciamis Regency - Kurniasih; Rika Sri Endah; Arie Budiawan; Ilham Maulana; Irfan Erfiana (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
Sukasetia Village in Cihaurbeuti District has great potential to be developed into a sustainable agrotourism destination. This study focuses on identifying agrotourism development strategies in the Sukapulang area using participatory methods involving local communities as the main stakeholders. This study used qualitative methods, including in-depth interviews, participant observation, and descriptive analysis. The results showed that agrotourism development can provide significant economic benefits, such as creating alternative sources of income and preserving local culture and traditions. In addition, agrotourism also increases community involvement and encourages sustainable tourism practices that are in line with global trends. However, there are several challenges, such as inadequate infrastructure, limited access to information, and less than optimal promotional strategies. This study recommends improving infrastructure, digital promotion, and capacity building programs to empower local communities. These strategies aim to ensure the sustainability and long-term competitiveness of agrotourism initiatives. The findings suggest that with collaborative efforts involving local communities, government, and the private sector, Sukasetia Village can become a model for community-based sustainable tourism development in rural areas, providing positive impacts on economic and social growth.